2019
DOI: 10.1186/s12864-019-6265-1
|View full text |Cite
|
Sign up to set email alerts
|

Infection and RNA-seq analysis of a zebrafish tlr2 mutant shows a broad function of this toll-like receptor in transcriptional and metabolic control and defense to Mycobacterium marinum infection

Abstract: BackgroundThe function of Toll-like receptor 2 (TLR2) in host defense against pathogens, especially Mycobacterium tuberculosis (Mtb) is poorly understood. To investigate the role of TLR2 during mycobacterial infection, we analyzed the response of tlr2 zebrafish mutant larvae to infection with Mycobacterium marinum (Mm), a close relative to Mtb, as a model for tuberculosis. We measured infection phenotypes and transcriptome responses using RNA deep sequencing in mutant and control larvae.Resultstlr2 mutant embr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 101 publications
(109 reference statements)
3
28
0
Order By: Relevance
“…Embryos of the tlr2 and myd88 mutants showed similar numbers of macrophages and neutrophils as their wild type siblings ( Figures 1B–E ). This result is consistent with our previous studies of the same myd88 mutant at 3 dpf and the tlr2 mutant at 2 dpf ( van der Vaart et al, 2013 ; Hu et al, 2019 ). With the aim of investigating the importance of the tlr2 and the myd88 mutations for leukocyte behavior under unchallenged condition, the CHT region was analyzed in the double transgenic lines of tlr2 and myd8 8 using CLSM by taking time-lapse images ( Figure 1A ).…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…Embryos of the tlr2 and myd88 mutants showed similar numbers of macrophages and neutrophils as their wild type siblings ( Figures 1B–E ). This result is consistent with our previous studies of the same myd88 mutant at 3 dpf and the tlr2 mutant at 2 dpf ( van der Vaart et al, 2013 ; Hu et al, 2019 ). With the aim of investigating the importance of the tlr2 and the myd88 mutations for leukocyte behavior under unchallenged condition, the CHT region was analyzed in the double transgenic lines of tlr2 and myd8 8 using CLSM by taking time-lapse images ( Figure 1A ).…”
Section: Resultssupporting
confidence: 94%
“…However, since TLRs have not been implied in sensing meandering gradients, we assume that this function involves other receptors. Tlr2 has been shown to be essential for the regulation of cytokines and chemokines expression in both mice and zebrafish ( Moles et al, 2014 ; Hu et al, 2019 ). For instance, we have shown that a tlr2 mutant shows a significant lower expression of cxcl11aa and also of a related chemokine, cxcl11ac , during mycobacterial infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interleukin-18 production can be stimulated following activation of NLRP6 [ 13 ]. Results of several studies suggest that TLR2 and interleukin-18 are at least partly involved in granuloma formation [ 14 , 15 ], and in vitro and in vivo models have indeed shown that C. acnes is able to induce granulomas [ 3 ]. It is therefore possible that C. acnes is not a specific trigger of sarcoidosis, HP and (E)GPA, but that its LTA contributes to inflammation and granuloma formation.…”
mentioning
confidence: 99%